Toward the Specific Criminal Procedures for Disabled Persons in Indonesia - Muhammad Amin (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2022)
This paper aims to analyze the need for the specific criminal procedure for disabled persons in Indonesian criminal justice system. This study employed doctrinal legal research using statute and conceptual approaches. The findings of this research reveal that the criminal justice system is based on the normalcy concept, which holds that everyone is physically and cognitively normal. As a result, the investigation, prosecution, and examination processes in court proceedings are exclusively aimed at and created for regular people. Persons with disabilities have been pushed to the margins and perhaps ignored. Persons with disabilities' rights are frequently infringed, both as perpetrators and as witnesses/victims of criminal activities. The medical method should be abandoned in favor of a social approach for the criminal justice system to be pro-people. What's needed is for law enforcement to do their jobs at each stage of the criminal justice system so that people with disabilities can have a fair trial. In the early phases of the criminal justice process, a profile assessment is required to determine the character, challenges, and requirements of people with disabilities.